The marketplace of democracy : electoral competition and American politics - McDonald, Michael, 1967-; Samples, John Curtis, 1956- (Washington, D.C. : Cato Institute : Brookings Institution Press, 2006)
Since 1998, U.S. House incumbents have won a staggering 98 percent of their reelection races. Electoral competition is also low and in decline in most state and primary elections. The Marketplace of Democracy combines the resources of two eminent research organizationsthe Brookings Institution and the Cato Instituteto address the startling lack of competition in our democratic system.
The marketplace of democracy : normative and empirical issues / Michael P. McDonald and John Samples -- Competition in U.S. Congressional elections / Gary C. Jacobson -- Competition in state legislative elections, 1992-2002 / Richard G. Niemi [and others] -- The decline of competition in U.S. primary elections, 1908-2004 / Stephen Ansolabehere [and others] -- Minor-party candidates in Congressional elections / Paul S. Herrnson -- The geography of electioneering : campaigning for votes and campaigning for money / James G. Gimpel and Frances E. Lee -- Direct democracy and electoral reform / John G. Matsusaka -- The place of competition in American election law / Nathaniel Persily -- Term limits : a recipe for more competition? / Bruce Cain, John Hanley, and Thad Kousser -- Redistricting and competitive districts / Michael P. McDonald -- Do public funding programs enhance electoral competition? / Kenneth R. Mayer, Timothy Werner, and Amanda Williams -- State campaign finance reform, competitiveness, and party advantage in gubernatorial elections / David M. Primo, Jeffrey Milyo, and Tim Groseclose -- The perfect electoral marketplace : "If men were angels ..." / Michael P. McDonald and John Samples.
Includes bibliographical references and index.
Print version record.
Electronic reproduction.
Master and use copy. Digital master created according to Benchmark for Faithful Digital Reproductions of Monographs and Serials, Version 1. Digital Library Federation, December 2002.
digitized
English.
Keywords: USA -- Government; Elections -- United States; Representative government and representation -- United States; Opposition (Political science) -- United States; Democracy -- United States; Élections -- États-Unis.; Gouvernement représentatif -- États-Unis.; Opposition (Science politique) -- États-Unis.; Démocratie -- États-Unis.; POLITICAL SCIENCE -- Political Process -- Elections; POLITICAL SCIENCE -- Political Process -- General; Democracy; Elections; Opposition (Political science); Representative government and representation; United States; Opposition; Demokratie